2014
DOI: 10.1073/pnas.1413204111
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase 1 inhibition reversibly impairs synaptic function

Abstract: Topotecan is a topoisomerase 1 (TOP1) inhibitor that is used to treat various forms of cancer. We recently found that topotecan reduces the expression of multiple long genes, including many neuronal genes linked to synapses and autism. However, whether topotecan alters synaptic protein levels and synapse function is currently unknown. Here we report that in primary cortical neurons, topotecan depleted synaptic proteins that are encoded by extremely long genes, including Neurexin-1, Neuroligin-1, Cntnap2, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 55 publications
(87 reference statements)
2
49
0
Order By: Relevance
“…Some of these long transcripts suppressed by CPT are linked to autism [25]. In CNs, many of these transcripts suppressed by CPT encode synaptic proteins and, as a result, excitatory and inhibitory neurotransmission is reversibility blocked by CPT [27]. These observations along with our study collectively highlight the importance of TOP1 in transcriptional regulation in neurons and could explain why they are more sensitive to TOP1 poisons like CPT and ActD.…”
Section: Discussionsupporting
confidence: 54%
“…Some of these long transcripts suppressed by CPT are linked to autism [25]. In CNs, many of these transcripts suppressed by CPT encode synaptic proteins and, as a result, excitatory and inhibitory neurotransmission is reversibility blocked by CPT [27]. These observations along with our study collectively highlight the importance of TOP1 in transcriptional regulation in neurons and could explain why they are more sensitive to TOP1 poisons like CPT and ActD.…”
Section: Discussionsupporting
confidence: 54%
“…Together these results suggest that topetecan acts directly on the upstream PWS SNORD116 locus to reduce transcript levels of the downstream UBE3A-ATS . The effects of topotecan are not specific for only the PWS/AS locus, as topetecan treatment of mouse neurons reduces the level of multiple synaptic genes, including many that are implicated in ASD such as Cntnap2, Nrxn3 , and Cntn5 [85, 86]. Although topotecan may not be a suitable therapy for AS because of this lack of specificity, these studies do establish that a small molecule approach to the regulation of UBE3A in human neurons would be plausible.…”
Section: Ube3a Deficiency In Angelman Syndromementioning
confidence: 99%
“…These findings suggested that a length-dependent impairment of gene transcription, particularly in neural tissues and neurons where longer genes are overrepresented (Figure 1, 2) (Gabel et al, 2015), might impair synaptic function and contribute to neurodevelopmental disorders. In support of this possibility, topoisomerase inhibition reversibly depletes Neurexin-1 and Neuroligin-1 at the protein level and reversibly impairs synaptic function (Mabb et al., 2014). …”
mentioning
confidence: 99%